1985
DOI: 10.3181/00379727-178-42053
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Filtration and Fluid Balance in Genetically Hypertensive Mice

Abstract: The Schlager genetically hypertensive mouse has been shown to be a valuable animal model with which to study human essential hypertension. Previous studies have characterized renal morphology, juxtaglomerular index, hematocrit, prostaglandin levels, brain catecholamines, social behavior, and patterns of inheritance. The present study continues the phenotypic characterization of this animal model. Using desiccation, isotope dilution, and clearance, the total body water, extracellular fluid volume, and glomerula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Genetic drift could be expected between this initial study and the present time, however, it is interesting to note that in this case kidney size is not necessarily linked to hypertensive status. Older studies comparing non-diabetic Schlager mouse strains also found that by 10–20 weeks of age hypertensive mice have less body fluid (as a percentage of body weight) than normotensive Schlager mice (Rosenberg et al, 1985). In the present study we found no significant differences between strains (with and without concomitant diabetes) for water intake or urine output at 18 weeks of age (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic drift could be expected between this initial study and the present time, however, it is interesting to note that in this case kidney size is not necessarily linked to hypertensive status. Older studies comparing non-diabetic Schlager mouse strains also found that by 10–20 weeks of age hypertensive mice have less body fluid (as a percentage of body weight) than normotensive Schlager mice (Rosenberg et al, 1985). In the present study we found no significant differences between strains (with and without concomitant diabetes) for water intake or urine output at 18 weeks of age (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Glomerular number then plateaus in BPH/2 mice, which have markedly fewer glomeruli in adulthood compared with BPN/3 mice. Total body water, used as a measure of volume expansion, was also greater in younger BPH/2 mice than BPN/3 but this trend reversed with age and resulted in a lower total body water in older mice (Rosenberg et al, 1985). When a comparison is made between glomerular number and total body volume, it is noticeable that total body volume only starts to decrease toward normal levels after glomerular number becomes lower in the BPH/2 mice.…”
Section: Heart Vessel and Kidney Structure And Functionmentioning
confidence: 99%
“…It is also possible that renal sympathetic hyperinnervation and increased AngII levels result in increased anti-natriuretic effects in BPH/2 mice. Rosenberg and colleagues measured glomerular filtration rate in mature BPH/2 mice and while it tended to be lower than in BPN/3 mice, this did not reach significance (Rosenberg et al, 1985). Furthermore, BPH/2 mice are reportedly not salt sensitive (Leckie, 2001).…”
Section: Neuropeptide and Neurosteroid Contribution To Hypertension Imentioning
confidence: 99%
See 1 more Smart Citation